Near fatal outcome following internal jugular vein catheterization for haemodylisis - Idris, Rahimah; Mohamad, Irfan (Bangladesh Journal of Medical Science, 2010)
In the recent years, the internal jugular vein has become the access route of choice for placement of hemodialysis catheters. The internal jugular vein is now the preferred route for dialysis access in the Dialysis Outcomes Quality Initiative guidelines. Neck hematoma following internal jugular vein catether insertion is uncommon, especially the one that leads to acute airway obstruction which is due to the progressively expanding neck hematoma DOI: 10.3329/bjms.v9i4.6690 Bangladesh Journal of Medical Science Vol.09 No.4 July 2010 pp.231-233